Penerapan Komunikasi Terapeutik Islami dalam Mengatasi Problematika Psikologis Siswa-Siswi di Madrasah - Hutama, Aprizaldi; Arifin, Isep Zainal; Satriah, Lilis (Jurnal komunikan, 2024)
Islamic therapeutic communication is a form of interpersonal communication between nurses and patients which aims to help the patient's healing or recovery process. This process is carried out by providing suggestions for interactions that support healing and help resolve patient problems, based on Islamic principles. The patients in question are madrasah students who face psychological problems due to pressure in the educational sector, such as minimum target demands, educational standards, diversity of student backgrounds, complexity of subject matter, and limited resources (competence, potential and educational costs). These things trigger stress and psychological problems. This research examines how Islamic therapeutic communication can overcome psychological problems experienced by madrasa students. Therapeutic communication will be more effective if educators are directly involved with students, especially through providing suggestions that strengthen spiritual aspects. With this approach, positive suggestions can help the healing process and overcome students' psychological problems. In this case, educators act as therapists by applying various communication techniques optimally, aiming to direct student behavior in a more positive direction through strengthening Islamic values.